2002
DOI: 10.1007/s00464-001-9201-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of dopamine in renal dysfunction during laparoscopic surgery

Abstract: An intrabdominal pressure of 15 mmHg induces a time-limited renal dysfunction, and low doses of dopamine could prevent this undesirable effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…Following a 30-min stabilization period, organs were randomly assigned to one of seven groups (n = 10), where they were exposed to intrachamber pressure of 3,5,8,12,15, or 18 mmHg. The seventh group was perfused under 0 mmHg, serving as pressure control.…”
Section: Isolated Perfused Kidney Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a 30-min stabilization period, organs were randomly assigned to one of seven groups (n = 10), where they were exposed to intrachamber pressure of 3,5,8,12,15, or 18 mmHg. The seventh group was perfused under 0 mmHg, serving as pressure control.…”
Section: Isolated Perfused Kidney Preparationmentioning
confidence: 99%
“…Materials and methods Seventy Wistar rat kidneys (n = 10 per group) were isolated. They were perfused with oxygenated, warm, Krebs-Henseleit solution containing 5% albumin within an isolated environment and subjected to various CO 2 pressures (0 [control], 3,5,8,12,15, and 18 mmHg) for 60 min. Half of each group was additionally perfused for 30 min at 0 mmHg pressure.…”
mentioning
confidence: 99%
“…Some previous studies, and even more recent ones, have shown an improvement in renal function in a variety of settings, such as situations of high intra-abdominal pressure during laparoscopy, 23 cardiac surgery, 24,25 refractory ascites due to cirrhosis, 26 liver transplantation, 27 general intensive care 28,29 or postoperative states. Some authors have even suggested that the responsiveness to LDD, as assessed by two-hour creatinine clearance, could be helpful in selecting patients who would benefit from its use.…”
Section: Discussionmentioning
confidence: 99%
“…The use of low dose Dopamine has been recommended earlier based on reported increase of renal perfusion during laparoscopic procedures [26], and has also been suggested in CRS and HIPEC [9,15]. However, the standardized use of furosemide [9] and low dose dopamine [6] is inadvisable as other studies have demonstrated no change in creatinine values during CRS and HIPEC with just maintenance of normovolemia and adequate urine output [2].…”
Section: Cardiovascular Systemmentioning
confidence: 92%